(untitled) (TAJ: Journal of Teachers Association, 2018)
The risk of diabetes mellitus and coronary heart disease is high among South-Asian population. In this study, our objective was to measure blood glucose level during acute coronary syndrome of previously known non-diabetic patients that will give the information about the frequency of acute hyperglycemia in acute coronary syndrome (ACS) among Bangladeshi population. It is an observational cross sectional study performed in Rajshahi Medical College Hospital. A total of 248 non-diabetic subjects with ACS got admitted into hospital. FBS and standard OGTT within 3 days of ACS were done. This study was done to find out glucose abnormalities among ACS patients. Out of 248 study population, 135(54.44%) had glucose abnormalities. Male was 87.10% (216). Among male, IGT (prediabetic) was 31.94% (69) and diabetic 24.54% (53). Mean age (±SD) of our study population was 51.71±11.84 years. Normal glucose tolerance (NGT) was found in 45.6% (113) cases, IGT (prediabetic) and diabetic were detected among 30.6% (76) and 23.8% (59) cases respectively. Non-diabetic Bangladeshi patients showed a high prevalence of hyperglycemia in acute coronary syndrome (ACS). We should create awareness about a new risk factor- acute hyperglycemia during acute coronary syndrome and take appropriate and effective measures to reduce morbidity as well as mortality as a consequence of acute hyperglycemia during ACS with or without diabetes. TAJ 2012; 25: 30-34